Saliva and Salivary Diagnostics - Gokul, Sridharan (IntechOpen, 2019)
Salivary diagnostics have advanced exponentially in the past decade. Saliva collection is easy and non-invasive and allows for detecting a myriad of biomarkers, making it a promising diagnostic tool. Salivary analytes have been evaluated for their role as potential biomarkers in oral cancer, cancer of distant sites, dental caries, periodontal diseases, oral microbial infections, and autoimmune disorders, as well as in diagnosis of systemic diseases. This book presents a thorough knowledge of the functions and properties of saliva, its role in health and disease, and the diagnostic technologies available for the identification of saliva biomarkers.